A multi-case study of the vertically integrated health-care at county-level in rural China: towards holistic and dynamic governance - Xu, Wenhui; Zhu, Li; Peng, Zixuan; Chen, Xu (Frontiers in Public Health, 2024)
Background In contrast to the Grading Diagnosis and Treatment System (GDTS), Vertically Integrated Health-care at County-level (VIHC) is a strategic policy in rural China. This research intends to analyze the shift in governance paradigm with regard to the adjustment of the power structure and interest relationships among various participants, using the building of VIHC as a cut-in point. Methods We carry out a multi-case study to investigate the paradigms of health governance when building VIHC in three different rural counties in China. Results There were exchanges between government and other participants, vertical and horizontal collaborations among government divisions, and prompt responses to public requirements. County C’s local administration, in particular, placed a strong emphasis on bureaucratic power and collaboration between various departments both within and outside of administrative boundaries. In contrast, County B’s local administration emphasized the independence of healthcare practitioners and worked to win their support. In contrast to the previous two governments, County A encouraged social actors to participate and saw a little improvement in performance. Conclusion In examining the health reform in rural China, this study paints a picture of the development of the health governance paradigm. In rural China, a comprehensive and dynamic governance paradigm was created through the integration of the health decision-making process, which was driven by the public’s health needs, the operation mechanism, which featured both competition and cooperation, and the action logic of sharing responsibility.